Some predators of the jellyfish (Rhopilema nomadica) entering the Gulf of Antalya - Gokoglu, Mehmet; Çağıltay, Ferhat; Yıldız, Alper (Universitas Malikussaleh, 2025)
Rhopilema nomadica, which was introduced to the Mediterranean ecosystem later, is a jellyfish species originating from the Indian Ocean. This jellyfish is distributed along the coasts of Pakistan, Mozambique and the Red Sea. R. nomadica, which is very abundant in Israel, Lebanon, Syria and the Gulf of Iskenderun, drifts westward from the open waters of the Gulf of Antalya between March and May with the main currents of the Mediterranean Some of these jellyfish enter the Gulf of Antalya and cause fear and anxiety for swimmers in the sea. During our Scuba dives to the world-famous cliffs of Antalya, it was observed that Bearded fire worm (Hermodice carunculata) gathered on the jellyfish at the bottom, preventing them from swimming by creating weight and consuming them as food. Again, within the scope of this study, it was determined that some jellyfish at the bottom were consumed by crabs (Charybdis hellerii). Photographs and video recordings of the interactions of these living creatures were taken. In this study, the interaction between jellyfish and their predators is presented. Keywords: Charybdis helleri; Gulf of Antalya; Hermodice carunculate; Rhopilema nomadica